Development of 3 Phase Pump Panel Monitoring System based on Internet of Things (Case Study PERUMDAM) - Ihsan, Muhammad; Al Muttaqi, Ahmad Rif'a; Ahmad, Umar Ali; Wicaksana, Jati Satria; Azmi, Fairuz (Universitas Telkom, 2022)
Water is the most basic human need. To maintain the distribution of water runs well, PERUMDAM uses a water pump panel to run and monitor the water pump to keep running. Even so, the water pump can be damaged at any time so PERUMDAM officers do routine activities to check the health of the water pump. Therefore, this article tries to solve the problem by making the design and implementing the IoT-based pump panels. An IoT-based pump panel is a device that is connected to an Android application to control and monitor the pump panel in real-time. In this study, NodeMCU is used as a center for sensor data retrieval to be sent to Firebase. Android applications can send notifications if there are anomalies in the sensor data. Controlling that can be done by the IoT-based pump panel is changing the mode on the analog pump panel from manual to automatic, and vice versa. The monitoring data obtained by the IoT-based pump panel is divided into two types. The optocoupler generates data related to the sensors on the analog pump panel in a boolean form. The power meter generates data in the form of values for voltage (R, S, T), current (R, S, T), frequency, and others as needed. The data obtained on the power meter can be used to calculate the power used by the analog pump panel.